Collective bargaining, decentralisation and crisis management in the German metalworking industries since 1990 - Reinhard Bispinck; Heiner Dribbusch (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2011)
Collective bargaining in the German metal and electrical engineering (M+E) industries has undergone a phase of considerable development since the 1990s. The profound changes which underwent collective bargaining in M+E over the last two decades have to be regarded against the background of a new global and national political and economic environment which emerged after the end of the Cold War. The M+E sector with at its core the automobile industry underwent successive waves of restructuring which shaped the bargaining agenda. This discussion paper examines these developments, putting a special focus on the changing bargaining agendas at both sectoral and company level and looks in particular at the decentralisation of collective bargaining. The management of the crisis of 2008 - 2010 in metal manufacturing is a further topic.A first version of this paper was presented at a meeting of the European GUSTO research project on 6 September 2011 in Barcelona. – – Die Tarifpolitik in der deutschen Metall- und Elektroindustrie hat seit den 1990er Jahren einen tief greifenden Wandel durchlaufen. Die Entwicklung der letzten zwei Jahrzehnte ist vor dem Hintergrund der Veränderungen in den globalen wie nationalen politischen und ökonomischen Rahmenbedingungen zu betrachten, die sich nach dem Ende des Kalten Krieges herausbildeten. Die Metall- und Elektroindustrie und insbesondere die Automobilindustrie erlebten aufeinander folgende Restrukturierungswellen, die die Inhalte der tariflichen und betrieblichen Aushandlungsprozesse prägten. Dieses Diskussionspapier untersucht diese Entwicklungen und die Veränderungen in der Betriebs- und Tarifpolitik, wobei besonders die Dezentralisierung der Tarifpolitik betrachtet wird. Das Krisenmanagement der Jahre 2008 bis 2010 in der Metall- und Elektroindustrie ist ein weiterer Punkt.Eine erste Version dieses Papier wurde am 6. September 2011 bei einem Treffen des europäischen GUSTO Forschungsprojekts in Barcelona vorgestellt.
Keywords: 330